Performance analysis of ERS using R134a - An experimental investigation (Part 2) – System design. Issue 1 (March 2021) - Kumar, Vikas; Tiwari, Sandeep; Sachdeva, Gulshan; Jain, Vaibhav; Devanshu,; Raghav, Paras; Nagar, Ankush; Uttam,
Abstract: The paper presents a mathematical model based on the 1-D gas dynamic equations used to calculate the design and dimensions of the ERS. In the model, the design of the heat exchangers i.e., generator, condenser and evaporator are calculated for the specified ejector geometry. Additionally, the fabrication methodology is also discussed in detail.